The efficacy and safety of evogliptin for type 2 diabetes mellitus: A systematic review and meta-analysis - Tang, Qizhi; Pan, Weiyu; Peng, Liangyue (Frontiers in Endocrinology, 2022)
Introduction: The dipeptidyl peptidase-4 inhibitor (DPP-4i) drugs such as evogliptin as the second-line drugs for type 2 diabetes mellitus (T2DM) treatment, has been reported to facilitate insulin secretion by reducing glucagon and inhibiting glucagon like peptides. With a vague consensus, the advantageous and non-inferior effects of evogliptin relative to other DPP-4i drugs were recently demonstrated on hemoglobin A1c (HbA1c) levels and overall adverse events in T2DM patients. Thus, the aim was to evaluate the overall influence of evogliptin on HbA1c levels and the adverse events in T2DM patients compared to sitagliptin and linagliptin. Methods: Complying with PRISMA guidelines, we conducted a systematic literature search in databases and a meta-analysis. Data about HbA1c levels and the adverse events of T2DM patients were collected and analyzed. Results: From 1,397 studies, we found five matched studies involving 845 subjects (mean age: 54.7 ± 3 years). The meta-analysis revealed that evogliptin was non-inferior to sitagliptin/linagliptin with a mean difference of 0.062 (95% CI: -0.092 to 0.215. I2: 0%. P = 0.431) regarding the HbA1c level reduction, and the risk ratio was -0.006 (95% CI: -0.272 to 0.260. I2: 1.7%. P = 0.966) regarding the adverse effects, indicating no significant difference between evogliptin and linagliptin or sitagliptin in affecting the HbA1c level and adverse effects. Conclusion: The study provides preliminary evidence regarding the similarity in the efficacy of evogliptin compared to other DPP-4i drugs, including sitagliptin and linagliptin, for managing HbA1c levels and adverse events.